Criminal Confrontation of Illicit Banking Operations: Terrorism Financing and Failure to Report Suspicious Financial Transactions - Abdulkarim Jasim, Researcher. Marwa; Hammad Hamid, Prof .Dr. Hasan (Basra studies journal, 2026)
The crime of terrorism financing through banking systems represents one of the most significant threats to financial institutions. Terrorist groups exploit banks to transfer illicit funds and secure the financing necessary to carry out their operations, using sophisticated methods to conceal the true source of funds. These methods may include the use of shell companies, complex financial transfers, or exploiting banking systems to give a legal façade to money intended for terrorist activities. The danger of this crime lies in its close connection to transnational criminal networks and its ability to blend into ordinary banking operations. In this context, the failure to report suspicious financial transactions has emerged as a distinct offense, committed by banking institutions or employees who intentionally or negligently refrain from reporting transactions that raise suspicion. This breach constitutes a failure to fulfill legal and regulatory obligations, thereby facilitating money laundering and terrorism financing and undermining the effectiveness of the national framework for combating these crimes.